방송플랫폼 융합의 국제적 흐름과 MCN에 대한 연구 -해외한국어방송사의 돌파와 지원을 위한 모색을 중심으로 - 장우린; Woo Rin Chang (기초조형학연구, 2016)
최근 새로운 방송 패러다임이 MCN을 통해 가시화되고 있다. 이는 디지털네트워크 상에서 다양화된 1인 또는 소규모 방송 플랫폼들이 통합되어 관리되는 시스템으로서, 현재 국가적으로 중요하지만 열악한 상황에 처해있는 해외한국어방송사들에게 특히 중요한 해결의 실마리를 제시하고 있다. 1인 또는 소규모 창작자들을 발굴하여 개인적인 선택과 취향에 더욱 근접한 맞춤형 콘텐츠로 특히 젊은 층의 시청자들을 엄청난 속도로 흡수하고 있는 MCN 기업들의 방법론은 기존 공중파와 케이블이 가진 중앙집중형 단방향 방송시스템과는 달리 방송에 있어서 쌍방향적 자가충족 구조를 가능하게 하는 ``프로슈머1)`` 계급을 부상시키고 있다. 게다가 각종 규제로부터 자유로운 프로슈머들은 그들의 삶과 밀착된 진솔한 방송콘텐츠를 생산, 주로 현재의 대중화된 모바일환경에 힘입어 노출시키는데, 이들에게 있어서 1인 또는 소규모 창작 환경은 오히려 시청자의 요구에 대하여 기동성 있는 대응이 가능한 긍정적 요소이다. 거대자본이 투입된 고전적인 방송체계를 훌쩍 뛰어넘는 인기와 시청자 참여도로써 MCN은 새로운 가능성을 제시하고 있다. 이미 국내외 많은 메이저급 방송사들이 이 MCN 분야에 많은 자본을 투입하고 있는 실정이다. 이러한 MCN의 패러다임을 또한 해외한국어방송사와 지원기관의 입장에 적용하는 본 연구는 해외한국어방송 시청자들과 제작자들에 대한 온, 오프라인 설문과 인터뷰가 이루어졌으며, 최근의 방송플랫폼 변화를 파악하기위해서 관련 세미나, 컨퍼런스, 연구보고서, 전문가 의견을 반영, 학술서적과 논문을 기초로 이해를 도모하였다. 이를 통하여 본 연구는 빅데이터 시대의 방송콘텐츠 소비에 있어서의 새로운 메커니즘이 본격적으로 작동하기 시작했음을 드러내려 하는 것이다. Recently, MCN(Multi Channel Networks2)) have emerged as a new paradigm of broadcast. MCN means a kind of network system which manages broadcasting platforms to unify; there are various one-man or small scale broadcast in the platform of digital network. Now, this MCN system gives a chance for overseas korean broadcasting companies to solve their inferior grade. The class called ``prosumer`` who is capable to create the broadcasting product not of centralized linear structure but of interactive self-satisfaction structure, owing to the MCN company`s methods which absorb dynamically young audiences with bespoke broadcasts aim at their individual taste; these broadcasting titles are able to be created only by one-man or small scale creators. Besides, being free from restrictions, these prosumers make honest broadcasting products reflecting their living, so their one-man or small broadcasting environment is rather suitable to step up to the plate and reply audience`s demands; these broadcasting products are showed mainly in mobile platform. Already, internally and externally, many major broadcasting companies have extensively invested in this area. Appling this paradigm of MCN to overseas korean broadcasting companies and support organizations, in this study, the survey and the interview are accomplished, and for understand recent changes about the broadcasting platform, one has explored informations from seminars, conferences, reports, specialists` advices; using books, and theses to ameliorate the understanding. This study would like to reveal that the serious running of new mechanism has started at the view point of broadcasting consumer in an age of big data.